2017
DOI: 10.5812/ijcm.9920
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA GHET1 Is Possibly Involved in the Pathogenesis of a Fraction of Breast Cancers

Abstract: Background: Breast cancer is the most frequently diagnosed cancer among women. Although several targeted therapies have been applied for patients with breast cancer, due to its heterogeneous nature, several patients do not benefit from these treatment modalities. Consequently, it is necessary to identify novel markers, which participate in the development of breast cancer. Recently, long non-coding RNAs (lncRNAs) have gained attention in this regard. Among them is lncRNA-gastric carcinoma high expressed transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…First, PCAT-1 was reported to be specifically overexpressed in prostate cancer. 12 Recently, its overexpression was gradually observed in breast cancer, 13 colorectal cancer, 10 esophageal squamous carcinoma, 14 bladder cancer. 11 Here, for the first time, we reported that PCAT-1 was accumulated in a subset of OC tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, PCAT-1 was reported to be specifically overexpressed in prostate cancer. 12 Recently, its overexpression was gradually observed in breast cancer, 13 colorectal cancer, 10 esophageal squamous carcinoma, 14 bladder cancer. 11 Here, for the first time, we reported that PCAT-1 was accumulated in a subset of OC tissues.…”
Section: Discussionmentioning
confidence: 99%
“…8 Further, the modulatory association of lncRNA and miR offers new perception of the molecular mechanisms during the onset and process of cancer. 9 To date, the overexpression of lncRNA prostate cancer-associated transcript 1 (PCAT-1) and its possible role have been reported in several cancers, [10][11][12][13][14][15] while studies about its role has not been conducted in OC.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PCAT-1 is effective in the EMT and Wnt/β-catenin signaling pathway [23]. Similarly, upregulated PCAT-1 has been found in breast cancer tissue [24].…”
Section: Discussionmentioning
confidence: 93%
“…A total of 12 eligible articles containing 761 patients with cancers were included in this meta-analysis after screening titles, abstracts or full texts. 18,21,22,[30][31][32][33][34][35][36][37][38] The process of article selection was shown in Figure 1.…”
Section: Literature Searchmentioning
confidence: 99%